The road to Rio: A brief report of training-load distribution of open-water swimmers during the Olympic season - Baldassarre, R.; Bonifazi, M.; Meeusen, R.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The 10-km open-water swimming race is an endurance event that takes place in lakes, rivers, or sea and has been an Olympic event since 2008. The aim of the present brief report is to describe training volume and intensity distribution of elite open-water swimmers during the 2016 Olympic season, verifying if, in order to maximize performance, most of the training would be performed at low intensities. Methods: Eight elite Italian open-water swimmers (3 male and 5 female; 25 [2] y, 1.74 [0.05] m, 68.26 [8.17] kg) specialized in distances between 5 and 25 km participated in the study. Training load was determined using an online training diary. Training intensity was categorized according to the 3-zone model: Z1, light intensity; Z2, moderate intensity; and Z3, high intensity. Session rating of perceived exertion was used to quantify training-intensity distribution. This method assigns the entire session into a single intensity zone based on the rating of perceived exertion recorded 30 min posttraining. Results: Total yearly training volume was 3576.93 (272.390) km (3220.80-4041.97), distributed across 446 (37) (397-484) sessions monitored during the 2016 Olympic season. Training-intensity distribution in each zone was 76.83% (8.11%) in Z1, 17.70% (6.79%) in Z2, and 5.47% (5.93%) in Z3. Conclusions: High volumes in Z1 appear to be an important training method used by elite open-water swimmers. However, future research is necessary to study the effects of different training-intensity distribution on open-water swimming performances.